OBJEKTIFIKASI SEKSUAL PADA PEREMPUAN DALAM FILM INDONESIA (ANALISIS SEMIOTIKA TERHADAP TOKOH AYU DAN ANAYA DALAM FILM SELESAI) - Ismi Putri Budiawan (2022)
This research is aimed to identify and describe sexual objectification of women towards the characters of Ayu and Anya from the movie, Selesai using Roland Barthes semiotic theory. The methods used for this research is descriptive qualitative with the use of primary and secondary data sources. Data collection techniques were carried out by observation, documentation, and sampling techniques. This study uses Roland Barthes' semiotic analysis by revealing the meaning of denotation, connotation, and myth as well as reading codes on the film by triangulating data sources. The final result of this study shows that there is an objectification of women in the film Selesai, according to Nussbaum there are 10 objectification points, namely Instrumentality, Denial Of Autonomy, Inertness, Fungibility, Violability, Ownership, Denial Of Subjectivity, Reduction To Body, Reduction To Appearance, and Silencing. Selesai fulfills the 10 points of objectification on the characters of Ayu and Anya sexually. With the fulfillment of these 10 points, while women in Indonesia and around the world are fighting for equal rights, Selesai breaks that struggle by depicting that women are weak and submissive to men.